PERANAN BERBAGAI JENIS BAHAN PEMBENAH TANAH TERHADAP STATUS HARA P DAN PERKEMBANGAN AKAR KEDELAI PADA TANAH GAMBUT ASAL AJAMU SUMATERA UTARA - Nurhayati Nurhayati; Razali Razali; Zuraida Zuraida (Jurnal Floratek, 2014)
The purpose of this research was to evaluate the influence of some types of soil ameliorans (lime, sea mud and some types of soil microorganisms) on P nutrient and soybean root development in peat soil.  The experiment was carried out in the Greenhouse of Agriculture Faculty of USU, Soil Biology Laboratory, Central Laboratory of Agriculture Faculty of USU and Laboratory of Soil analysis at RISPA, from March to November 2011.  The experiment was arranged in a completely randomized design, consisted of 13 treatments and two replicates. The treatments included control, dolomite lime, sea mud, lime + sea mud, Bradyrhizobium, mos, Mycorrhizal isolate of peat soil, mycorrhizal isolate of mineral soil, Bradyrhizobium + mos, mos + mycorrhizal isolate of peat soil isolates, mos + mineral soil mycorrhizal isolate, Bradyrhizobium + mos + mycorrhizal isolate of peat soil, Bradyrhizobium + mos + mycorrhizal isolate of mineral soil. Variables observed included soil pH, soil P available, plant P uptake, and weight of root dry. Types of amelioran exerted significant effect on soil pH, but did not exert significant effects on soil P available,  plant P uptake, and weight of dry root.